Synthesis of Ni(II) and Zn(II) Porphyrin Complexes for Hemoglobin Stabilization and Anti-Hemolytic Activity: In Vitro Studies, ADMET Prediction, Molecular Docking, and Molecular Dynamics An - HADJ AMMAR Yousra; MENNAI Nihal; MESSAI BOUBAKER Soundes; RAHAL Amina (. جامعة الوادي.Université d'EL-Oued., 2025)
This study aims to investigate the effect of four porphyrin derivatives on hemoglobin, given the importance of their ability to bind to heme-containing proteins and influence their functions. The research focused on evaluating the potential of these four porphyrin derivatives as therapeutic agents by assessing their ability to modulate oxidative stress and hemolysis. In vitro experiments were conducted, and the chemical structures of the compounds were confirmed using various analytical techniques, including cyclic voltammetry, UV-Vis spectroscopy, and nuclear magnetic resonance (NMR). The results showed that all four derivatives bind to hemoglobin with varying degrees of effectiveness. The compound TbiPPH₂ exhibited the strongest binding, with an IC₅₀ value of 28.57 µg/mL, while ZnTPPH₂ showed the weakest (IC₅₀ = 45.95 µg/mL). In terms of binding constants and free energy, NiTPPH₂ demonstrated the highest binding constant and the most favorable ΔG value (-23.48 kJ/mol), indicating a strong and spontaneous interaction. Regarding anti-hemolytic activity, NiTPPH₂ also showed the lowest half-maximal inhibitory concentration (IC₅₀), followed by TPPH₂. Molecular docking simulations supported these findings, revealing stable interactions with hemoglobin, with NiTPPH₂ being the most stable, showing a ΔG value of -31.12 kJ/mol, in agreement with the experimental data. Porphyrin derivatives, particularly NiTPPH₂, exhibit strong binding to hemoglobin and offer effective protection against hemolysis, making them promising candidates for therapeutic applications targeting oxidative stress and the preservation of red blood cells.
Toxicology
Keywords: TbiPPH2; ZnTPPH2; NiTPPH2; TPPH₂; hemolysis; hemoglobin; IC₅₀; porphyrin derivatives